Peace Education and Its Discontents: An Evaluation of Youth, Violence, and School-based Peace Programs in Northern Uganda - Jayanni Webster (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2013)
This research paper discusses current efforts and programs designed to address the issues of peace and conflict resolution, post-war recovery and education in northern Uganda. Through the collection of stories of life after war, I examine the experiences of children and youth and pilot peace education programs in secondary and primary schools. Northern Uganda was the site of a brutal civil war waged between the rebel group, the Lord’s Resistance Army, and the government’s Uganda People’s Defense Force. The war resulted in the mass abduction of children and the forced displacement of the northern population into internally displaced persons’ camps. Although active combat ended in a 2006 cease-fire, there are still challenges and lessons to be learned that could aid in understanding the conditions that give rise to violent uprisings and movements and in turn mitigate those conditions for a healthier society. In addition, a decade of displacement has birthed various tensions between the youth and adults in the face of changing customs and the return of abducted children. The young people of northern Uganda occupy a unique position in their communities given the role they played in the war, their potential part in reconstruction process, and their national calling as “the pillars of tomorrow’s Uganda.” The government and international organizations, recognizing a need to remedy factors that could lead to a relapse into conflict, developed peace education programs with the goal of creating a “culture of peace” in the region. My fieldwork focuses on two such programs and this paper explores early attempts and outcomes to implementing these programs in schools. With conceptual issues surrounding peace education philosophy, practice and policy, I argue that these programs encourage, rather, a “culture of complacency” in the face of a harsh economic and sociopolitical reality for Ugandan children and youth.
Keywords: Youth Violence; Peace Programs; Northern Uganda